Importance of Green Building Rating System on Modify Green Building: Addressing the Lack of Rating System for Restored Green Buildings in Rural Areas (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In India, over 65 populations are living in village. Comparing the overall population of India this number is large. Also they make their own houses either by own methods or by some persons who are experts from Construction Industry. There houses have some period to sustain on earth, after the completion of that period, either they are not feasible to live in or they get demolished by us. But if proper restoration is applied on them then they are ready to sustain more year on earth. Here we have to recycle the material to reduce overall building cost. For Eco Friendly Construction, in India, there are 2 rating systems. In GRIHA, all parameters which related to Green Building Construction are considered and which indicating the saving and reutilization of building material product, Energy saving etc. In LEED also almost same part is considered. There are some changes in parameter and final rating system is slightly different but that rating systems does not rate the restored structure. Restored structure is completely based on previous building part and addition of some new part using some old as well as new techniques. In both rating system they give some points and guidance related to recycle of material but main part is that building should be newly constructed or new construction should be there. There is no any a single clause related to the restored building, so we can’t identify our restored structure is Green Building or not. So this paper focus on restored structure in village area and why that structure is Green Building and which clauses should introduce in Green Building Rating System for Restoration of Structure.